2020
DOI: 10.3390/ijms21238917
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 Is Downregulated in Human Stenotic Aortic Valves and Its Inhibition Promotes Dystrophic Calcification

Abstract: Calcific aortic valve disease (CAVD) is the result of maladaptive fibrocalcific processes leading to a progressive thickening and stiffening of aortic valve (AV) leaflets. CAVD is the most common cause of aortic stenosis (AS). At present, there is no effective pharmacotherapy in reducing CAVD progression; when CAVD becomes symptomatic it can only be treated with valve replacement. Inflammation has a key role in AV pathological remodeling; hence, anti-inflammatory therapy has been proposed as a strategy to prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…In fact, inhibition of the enzyme by celecoxib, along with genetic depletion in the Klotho deficient mice (a known model of valve calcification) reduced calcification of the valve and of animal-derived VICs in vitro (32). On the other hand, a word of caution about the therapeutic potential of COX-2 inhibition by the celecoxib has been also raised by other studies, showing that in human VICs from stenotic valves treatment with the drug may increase the so-called dystrophic calcification, a process mediated by TGF-β1 and related to VICs myofibroblast differentiation and apoptosis (27,(33)(34)(35)(36). Early histological studies on 347 surgically excised aortic valves showed that 83% of them presented dystrophic calcifications, while lamellar bone with active bone remodeling were observed in only 13% (37).…”
Section: From Inflammation To Valve Degeneration: the Main Playersmentioning
confidence: 99%
“…In fact, inhibition of the enzyme by celecoxib, along with genetic depletion in the Klotho deficient mice (a known model of valve calcification) reduced calcification of the valve and of animal-derived VICs in vitro (32). On the other hand, a word of caution about the therapeutic potential of COX-2 inhibition by the celecoxib has been also raised by other studies, showing that in human VICs from stenotic valves treatment with the drug may increase the so-called dystrophic calcification, a process mediated by TGF-β1 and related to VICs myofibroblast differentiation and apoptosis (27,(33)(34)(35)(36). Early histological studies on 347 surgically excised aortic valves showed that 83% of them presented dystrophic calcifications, while lamellar bone with active bone remodeling were observed in only 13% (37).…”
Section: From Inflammation To Valve Degeneration: the Main Playersmentioning
confidence: 99%
“…The resident cells are also different: vascular smooth muscle cells (VSMCs) for the vessels and valve interstitial cells (VICs), essentially fibroblasts, for the valve. These are the cells that, under pathologic conditions, may undergo myofibrogenic [4], osteogenic, and even chondrogenic differentiation [5].…”
Section: Diversity In Vascular Versus Valvular Calcificationmentioning
confidence: 99%
“…Aortic valve stenosis is currently the most common valvular heart disease, and to date, there are no effective therapies to prevent or slow down the progression of this pathology ( Minamino-Muta et al, 2017 ). Alteration of functions of ECs, SMCs, and valve interstitial cells (VICs), which form the aortic valve, all contribute to its calcification ( Rutkovskiy et al, 2017 ; van der Ven et al, 2017 ; Vieceli Dalla Sega et al, 2020 ).…”
Section: Notch In Calcific Aortic Valve Diseasementioning
confidence: 99%